2011
DOI: 10.3109/13561820.2011.592229
|View full text |Cite
|
Sign up to set email alerts
|

Simulated interprofessional education: An analysis of teaching and learning processes

Abstract: Simulated learning activities are increasingly being used in health professions and interprofessional education (IPE). Specifically, IPE programs are frequently adopting role-play simulations as a key learning approach. Despite this widespread adoption, there is little empirical evidence exploring the teaching and learning processes embedded within this type of simulation. This exploratory study provides insight into the nature of these processes through the use of qualitative methods. A total of 152 clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 23 publications
4
61
1
1
Order By: Relevance
“…[18,19] We agree with Fenske et al's (2013) [20] perspective that participants attributes are innate and often come to the simulation experience with anxiety, self-confidence or lack of, and therefore; impact the overall simulation experience. [21] However, this concept also applies to the SP as the SP's age, ethnicity, and gender and knowledge about the subject may determine if the simulation is authentic.…”
Section: Theorycontrasting
confidence: 33%
“…[18,19] We agree with Fenske et al's (2013) [20] perspective that participants attributes are innate and often come to the simulation experience with anxiety, self-confidence or lack of, and therefore; impact the overall simulation experience. [21] However, this concept also applies to the SP as the SP's age, ethnicity, and gender and knowledge about the subject may determine if the simulation is authentic.…”
Section: Theorycontrasting
confidence: 33%
“…Assessing an acutely ill patient was directly relevant to the curriculum objectives being addressed by both 3'^'' year medical and nursing students during their time at Lincoln, Therefore, a teaching intervention to address team working in the context of acute illness, involving both 3"' year medical and nursing students, was identified as a potentially valuable addition to the teaching programme for both groups. Simulation has been used to deliver IPL (van Soeren et al,, 2011), and there is evidence to support the use of simulation to improve team working (Buljac-Samardzic, Dekker-van Doorn, van Wijngaarden, & van Wijk, 2010). Simulation was chosen as the tool for the delivery of IPL, An 'ice breaker' activity was used at the start of the session to reduce the stress associated with simulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited research on interprofessional simulation, with the most common being found among nursing and medical professions (Baker et al, 2008;Dillon et al, 2009;Maxson et al, 2011;Reese, Jeffries, & Engum 2010;Reising, Carr, Shea, & King, 2011), and nursing and paramedics (van Soeren et al, 2011;van Soeren, Devlin-Cop, MacMillan, & Reeves, 2012). Only a few others have reported on projects involving other health professions.…”
Section: Interprofessional Simulationmentioning
confidence: 99%
“…Only a few others have reported on projects involving other health professions. They include pharmacy (Barnett, Hollister, & Hall, 2011;Ruth-Sahd, Schneider, & Strouse, 2011), dietician (Hall, Marshall, Weaver, Boyle, & Taniguchi, 2011;Prentice, Taplay, Horsley, Payeur-Grenier, & Belford, 2011;van Soeren et al, 2011) social work Prentice, et al, 2011), occupational therapy Ruth-Sahd et al, 2011), audiology (Barnett et al, 2011), and physiotherapy .…”
Section: Interprofessional Simulationmentioning
confidence: 99%